2021
DOI: 10.1021/acsanm.1c00510
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Modulated CuMnOx Nanosheets as Catalysts for Toluene Oxidation

Abstract: Controllable ternary Pt–Cu–Mn lamellar oxides with different amounts of Pt were synthesized using a facile and expeditious self-propagating flaming technique for catalytic oxidation of toluene. The surface structure, composition, and structure–performance relationship were investigated by combining X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) surface area, scanning electron microscopy (SEM), transmission electron microscopy (TEM), hydrogen temperature-programmed reduction (H2-TPR), and X-ray photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It was widely accepted that the physical and chemical properties, such as component of active phase, specific surface area, Mn valence, concentration of adsorbed oxygen/lattice oxygen and reduction ability, can command the activity of the catalyst [48]. For the component factor of the active phase, we found that the ratio of Mn/Zr and their synthesis routes play a vital role in adjusting the content of active centers, and a low molar ratio (<2/3) of Mn/Zr would lead to the formation of a solid solution of Mn x Zr 1−x O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It was widely accepted that the physical and chemical properties, such as component of active phase, specific surface area, Mn valence, concentration of adsorbed oxygen/lattice oxygen and reduction ability, can command the activity of the catalyst [48]. For the component factor of the active phase, we found that the ratio of Mn/Zr and their synthesis routes play a vital role in adjusting the content of active centers, and a low molar ratio (<2/3) of Mn/Zr would lead to the formation of a solid solution of Mn x Zr 1−x O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the catalytic activity of the Mn oxide catalysts is affected by their physical and chemical properties, such as the active component, specific surface area, the valence state of Mn, and the surface adsorbed oxygen or lattice oxygen concentration [7]. In this work, the x%Mn-Pal catalysts were successfully obtained.…”
Section: Discussionmentioning
confidence: 91%
“…Up to date, researchers have developed a variety of catalysts for the removal of VOCs, mainly including precious metal materials [6,7] and transition-metal oxides [8,9]. Although the noble metal catalysts display excellent properties, the problems of high cost, easy sintering, and poisoning have not been effectively solved, which limit their further practical applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…A major part of such studies has been committed to the exploration of transition metals (Mn, Fe, Co, Ni, and Cu) oxides and rare earth metal (La and Ce) oxides. 5,6 Of these oxides, the catalysts formed by Co 3 O 4 , or CuO and CeO 2 , were shown to exhibit excellent catalytic activities for toluene oxidation. 7,8 Surface oxygen vacancies have received wide attention, which is due to their key roles in heterogeneous catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have, therefore, been performed with a focus on the replacement of precious metals by the design and syntheses of catalysts containing nonprecious metal oxides. A major part of such studies has been committed to the exploration of transition metals (Mn, Fe, Co, Ni, and Cu) oxides and rare earth metal (La and Ce) oxides. , Of these oxides, the catalysts formed by Co 3 O 4 , or CuO and CeO 2 , were shown to exhibit excellent catalytic activities for toluene oxidation. , …”
Section: Introductionmentioning
confidence: 99%